التفكير الإبداعي وعلاقته بالدافعية للتعلم لدى تلاميذ السنة الأولى ثانوي - تجاني, رحمة (University of Eloued جامعة الوادي, 2021)
الملخص: استهدفت هذه الدراسة تحديد علاقة التفكير الإبداعي بالدافعية للتعلم لدى تلاميذ مستوى الأولى ثانوي. كما استهدفت الدراسة التعرف على الفروق بين الذكور والإناث في كل من التفكير الإبداعي والدافعية للتعلم. وقد كانت فرضيات الدراسة كالتالي:  توجد فروق ذات دلالة إحصائية في التفكير الإبداعي لدى تلاميذ السنة الأولى ثانوي باختلاف الجنس.  توجد فروق ذات دلالة إحصائية في الدافعية للتعلم لدى تلاميذ السنة الأولى ثانوي باختلاف الجنس.  توجد فروق ذات دلالة إحصائية في التفكير الإبداعي لدى تلاميذ السنة الأولى ثانوي باختلاف الشعبة.  توجد فروق ذات دلالة إحصائية في الدافعية للتعلم لدى تلاميذ السنة الأولى ثانوي باختلاف الشعبة. وتوصلت الدراسة من خلال اختبار الفرضيات إلى عدة استنتاجات تأكد الارتباط الوثيق بين هاذين المتغيرين، وعلى وجود مستوى مرتفع لكليهما، حيث أن دافعية التعلم تتحقق بوجود تفكير إبداعي الى جانب عدة عناصر أخرى، كتشجيع الطلاب والاستماع لمطالبهمومخاوفهم في المدرسة Abstract: This study aimed to determine the relationship of creative thinking with motivation to learn among third-grade secondary school students..... The study also aimed to identify the differences between males and females in both creative thinking and motivation to learn. The hypotheses of the study were as follows: * There are statistically significant differences in the creative thinking of first year secondary school students according to gender. * There are statistically significant differences in the motivation to learn among first year secondary school students according to gender. * There are statistically significant differences in the creative thinking of first year secondary students according to the division. * There are statistically significant differences in the motivation to learn among first year secondary students according to the division. By testing the hypotheses, the study reached several conclusions that confirmed the close relationship between these two variables, and the existence of a high level for both, as the learning motivation is achieved by the presence of creative thinking along with several other elements, such as encouraging students and listening to their demands and fears at school.
دراسة ميدانية لتلاميذ السنة الأولى ثانوية بثانوية مفدي زكريا بالبياضة ولاية الوادي
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: التفكير الإبداعي، الدافعية للتعلم; Pensée créative, motivation à apprendre; Creative thinking, motivation to learn